Experiencia humana y mestizaje cultural en la sociedad de la información - García Carrasco, Joaquín (2011)
Both spatial mobility and change of settlements embody the necessary conditions for crossbreeding (mestizaje). Day after day, the relevance of the contents, proceedings, attitudes and values of the so -called “cross-cutting” subjects in the curricula seem more obvious, among them, “Intercultural Education”. This “cross-cutting” nature nurtures itself precisely from the fundamental elements that Henri van der Leer called “twentieth-century humanities”. Nowadays, three social processes are revitalizing the problem: migration movements and their consequences, the flourishing of nationalism and cultural entrenchments and the self-asserted appearance of a new world made up of information that, similar to a black hole, seems to absorb everything in a hitherto unheard of globalization. In this situation of generalized intercultural contact, the encouragement of a plural and open mentality becomes a basic education goal. To develop that mentality I propose six content organizers, six frames to foster attitudes, six criteria on which to build strategies, positions from which the value of social understanding among different citizens can be unraveled.